Contribution of NGOs Toward Promoting the Social-Economic Wellbeing of People in Kitumba Sub-County Kabale District: A Case Study of Raising the Village. - Ahebwa, Sam (2024)
The study assessed the contribution of NGOs toward promoting the social-economic wellbeing of people in Kitumba sub-county, Kabale district. a case study of Raising the Village following the study objectives which were; to examine the contribution of NGO's to the social-economic well-being of people in Kitumba sub-county, Kabale District, to assess the relationship between NGO activities and the social-economic well-being of people in Kitumba sub-county, Kabale District and to establish the socioeconomic factors affecting the well-being of the people in Kitumba sub-county, Kabale District. A descriptive research design was used across a sample of 50 respondents. Data collection tools were questionnaires and interviews. The results of the study revealed that NGOs have promoted community development by sensitizing community members to different development programs such as agriculture. The study concluded that Raising the Village projects have benefited 76.3% of respondents, primarily from education and agriculture, leading to sustainability promotion. Members also benefitted from water tanks, financial literacy, employment, and agricultural input. The study reveals that 62.3% of Kitumba sub-county, Kabale district residents own their homes, but many earn less than 100,000 a month, indicating low incomes. Despite access to healthcare from government facilities, many lack leadership roles and struggle to support their children's education. The study recommended that there is a need for the government to work together with Raising the Village to ensure that programs meant by the government to uplift its people are shared to ensure transparency in socio-economic development.